2011
DOI: 10.1126/science.1201730
|View full text |Cite
|
Sign up to set email alerts
|

Different B Cell Populations Mediate Early and Late Memory During an Endogenous Immune Response

Abstract: Memory B cells formed in response to microbial antigens provide immunity to later infections; however, the inability to detect rare endogenous antigen-specific cells limits current understanding of this process. Using an antigen-based technique to enrich these cells, we found that immunization with a model protein generated B memory cells that expressed isotype-switched immunoglobulins (swIg) or retained IgM. The more numerous IgM+ cells were longer lived than the swIg+ cells. However, swIg+ memory cells domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

54
654
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(716 citation statements)
references
References 26 publications
(34 reference statements)
54
654
7
1
Order By: Relevance
“…Given the functional heterogeneity of memory B-cell subsets (e.g., IgM + vs. IgG1 + memory B cells) (29,30), it is possible that each subset might differentially contribute to activation of T FH memory cells. Thus, better understanding of the regulatory mechanisms in the interactions of these memory B-cell subsets and T FH memory cells should provide important insights for development of better vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Given the functional heterogeneity of memory B-cell subsets (e.g., IgM + vs. IgG1 + memory B cells) (29,30), it is possible that each subset might differentially contribute to activation of T FH memory cells. Thus, better understanding of the regulatory mechanisms in the interactions of these memory B-cell subsets and T FH memory cells should provide important insights for development of better vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that MCMV induces poor CD8 T-cell response to challenges with emerging viral infections and that this poor response correlates to the frequency of the (Dogan et al, 2009;Pape et al, 2011;Tomayko et al, 2010). IgM memory B-cells persist long after the clearance of an infection, whereas the conventional memory cells are described as the frontline responders to infections (Good-Jacobson and Tarlinton, 2012).…”
Section: Effects Of Latent Infections On the Peripheral Memory B-cellmentioning
confidence: 99%
“…IgM+) memory cells (NSM; CD27+IgD+) [8]. During secondary antigen exposure SM B-cells proliferate rapidly and differentiate into antibody secreting cells, while NSM cells are able to reinitiate GC reaction and replenish SM fraction [9,10]. Because B-cell response to nuclear auto-antigens requires T-cell help, formation of pathogenic autoantibodies in SLE (e.g.…”
Section: Introductionmentioning
confidence: 99%